Guillain Barré syndrome in a population less than 15 years old in Brazil - Dias-Tosta Elza; Kückelhaus Carlos Santos (Arquivos de Neuro-Psiquiatria)
To know the impact of the Guillain Barré syndrome (GBS) in the population less than 15 years old, after the eradication of poliomyelitis. Data bank from the program of epidemiological surveillance of acute flaccid palsies (AFP) from the Fundação Nacional de Saúde were analyzed between 1990 -- 1996. From 3619 notifications of AFP there were 1678 GBS. GBS yearly incidence rates is 0.39-0.63 cases/100,000. No consistent seasonal variation existed or relationship to vaccines. Weakness at inclusion were, moderate 52.1%, severe in 47.9%, sixty days after 57.1% normal, 7.4% mild, 15.7% moderate, 10.4% with severe deficits, death in 5.4%. 67 (4.0%) cases unknown. Death rates varies from 2.8% in southeast to 7.9% in the northeast. GBS was the most frequent cause of AFP. In spite of the severity of this disease being similar in the different regions, the outcome varies according to origin of the cases, possibly reflecting the economical conditions in those places.